Exploring The Strategic Decision-Making Process Of Startup Founders Conducting Business Pivots When Facing Significant Decreases In Local Market Demand - Henik Hari Astuti; Ferby Claudia; Muhammad Firmansyah (STEBIS Bina Mandiri, 2026)
This research investigates the strategic decision-making process of startup founders who undertake business pivots in response to a significant decline in local market demand. In the volatile landscape of the digital economy, the ability to pivot is often a prerequisite for survival; however, the cognitive and organizational mechanisms behind this strategic shift—especially when triggered by shrinking local demand—remain under-explored in qualitative economic literature. This study aims to fill this gap by deconstructing how founders interpret market signals, evaluate existing resources, and ultimately decide to alter their core business models. Using a qualitative approach with a multiple-case study design, this research involved in-depth interviews with startup founders from various sectors who successfully or partially navigated a pivot within the last years. Data were analyzed using thematic analysis to identify recurring patterns in the decision-making process. The findings reveal that the decision to pivot is not merely a rational-economic response to declining revenue but is heavily influenced by